Bioturbation: a fresh look at Darwin's last idea - Meysman, Filip J.R.; Middelburg, Jack J.; Heip, Carlo H.R. (Trends in ecology & evolution (Amsterdam), 2006)
Bioturbation refers to the biological reworking of soils and sediments, and its importance for soil processes and geomorphology was first realised by Charles Darwin, who devoted his last scientific book to the subject. Here, we review some new insights into the evolutionary and ecological role of bioturbation that would have probably amazed Darwin. In modern ecological theory, bioturbation is now recognised as an archetypal example of ‘ecosystem engineering’, modifying geochemical gradients, redistributing food resources, viruses, bacteria, resting stages and eggs. From an evolutionary perspective, recent investigations provide evidence that bioturbation had a key role in the evolution of metazoan life at the end of the Precambrian Era.